A computer vision-based vibration measurement method for wind tunnel tests of high-rise buildings. Issue 182 (November 2018) - Huang, Mingfeng; Zhang, Baiyan; Lou, Wenjuan
Abstract: This paper presents a computer vision-based vibration measurement (VVM) method for wind tunnel tests of typical aeroelastic high-rise building models. After reviewing the existing vision-based measurement techniques, an advanced object-tracking algorithm, so called the template-corner algorithm, is developed to achieve more accurate vibration measurements in wind tunnel setups. Based on the newly developed object-tracking algorithm, the proposed VVM method can measure wind-induced dynamic displacements and acceleration responses, as well as identify dynamic model characteristics. The method is cost effective and can acquire all horizontal responses at the top plane of the building model under various wind angle conditions using only one complementary metal-oxide-semiconductor (CMOS) camera, with significant flexibility and adequate resolutions. A free vibration test and a series of wind tunnel tests for a typical aeroelastic high-rise building model were conducted to validate the proposed vision-based method. The results obtained from the proposed method were carefully compared with those from conventional measurement techniques using a laser displacement sensor and an accelerometer. The comparison results confirm the accuracy and feasibility of the VVM method for obtaining wind-induced dynamic responses of aeroelastic tall building models. Highlights: A computer vision-based vibration measurement (VVM) method is proposed for wind tunnel tests. The VVM method is accurate and cost effective. Wind-induced displacement and acceleration responses can be measured simultaneously.